2015
DOI: 10.1186/s12886-015-0052-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of outdoor activity on myopia onset and progression in school-aged children in northeast china: the sujiatun eye care study

Abstract: BackgroundDue to its high prevalence and associated sight-threatening pathologies, myopia has emerged as a major health issue in East Asia. The purpose was to test the impact on myopia development of a school-based intervention program aimed at increasing the time student spent outdoors.MethodsA total of 3051 students of two primary (grades 1-5, aged 6-11) and two junior high schools (grades 7-8, aged 12-14) in both urban and rural Northeast China were enrolled. The intervention group (n = 1735) unlike the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
187
1
14

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(207 citation statements)
references
References 42 publications
(43 reference statements)
5
187
1
14
Order By: Relevance
“…; Jin et al. ). For the cross‐sectional studies, if the exposure variable was defined as hours per day, results were standardized to hours per week by dividing the log(OR) and SE by 7 (Sherwin et al.…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…; Jin et al. ). For the cross‐sectional studies, if the exposure variable was defined as hours per day, results were standardized to hours per week by dividing the log(OR) and SE by 7 (Sherwin et al.…”
Section: Methodsmentioning
confidence: 98%
“…() and Jin et al. (), the additional time outdoors in the intervention group was considered the increase in time between the intervention and control groups, whereas in that by Wu et al. () the exposure was assumed from the time children were not allowed to stay in their classrooms.…”
Section: Methodsmentioning
confidence: 99%
“…Recent epidemiological studies indicate that outdoor activity (with increasing light exposure) affects mainly the onset of myopia but not the progression of myopia development in children, indicating a possible effect of DA signaling on initiation of myopia (Guo et al, 2013; He et al, 2015; Jin et al, 2015). Data from mouse models with retinal pathway defects that result in decreased dopamine turnover and increased myopia susceptibility would also support the hypothesis that DA release alters myopia induction (Figure 2).…”
Section: Challenges In Understanding the Role Of Da Signaling In Mmentioning
confidence: 99%
“…The etiology of myopia remains unknown, but some epidemiological studies have suggested that increased near vision tasks such as reading, using computers and smartphones are possible risk factors (Ip et al, 2008). Recently, the time spent outdoors was proposed as a protective factor (French et al, 2013a, French et al, 2013b, Guggenheim et al, 2012, Ip et al, 2008, Jin et al, 2015, Jones-Jordan et al, 2014, Jones et al, 2007, Read et al, 2014, Rose et al, 2008), and the beneficial effect of high ambient light for the protection of myopia has been confirmed in chicks, mice, and monkeys (Karouta and Ashby, 2015, Norton and Siegwart, 2013, Smith et al, 2012, Stone et al, 2013, Tkatchenko et al, 2013). Additionally, some clinical trials indicated that increased outdoor activity of students had an anti -myopia effect (He et al, 2015, Jin et al, 2015, Wu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%